Scalable Cloud Architecture for Variable Traffic Management: Insights from a Leading Travel Platform - Suchismita Das (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines Airbnb’s sophisticated approach to managing seasonal traffic fluctuations across its global travel platform. This article presents an in-depth analysis of the company’s cloud-native infrastructure, highlighting the critical role of Kubernetes in orchestrating dynamic resource allocation during peak periods. This article explores Airbnb’s innovative implementation of distributed caching mechanisms and database optimization techniques, which together form a robust foundation for handling surge capacity. This article investigates the platform’s comprehensive monitoring systems and incident response frameworks, revealing how proactive performance management contributes to system reliability. Special attention is given to Airbnb’s disaster recovery strategies and their integration with scalable cloud architecture. This article provides valuable insights into how modern travel platforms can maintain service quality and user experience while managing significant traffic variations, offering practical applications for similar large-scale digital services.